Etika Kebijakan Publik Pada Program Keluarga Harapan di Kota Palopo - Didik Iskandar (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
Ethics is one approach that is often used in public policy in the framework of public administration. The Family Hope Program is an empowerment program for underprivileged communities by providing conditional cash assistance. This study will to describe the benefits, great benefits, and benefits for as many people as possible in terms of the ethical perspective of utilitarianism from a policy in the form of a program, namely, implementation of the family of hope program in Palopo City. The object of this research is was family hope program at Palopo City. This study uses an evaluation method through a qualitative approach. Data obtained through data presentation, data reduction, verification and conclusion drawing. The results of the study indicate that the benefits obtained to implementation of family hope program in Palopo City are based on utilitarian ethics, namely there are additional costs in meeting education and health needs. Furthermore, great benefit that can be obtained to program recipients is a change in mindset to prioritize and care more about the importance of children's education and in the health sector, namely the importance of regular check-ups to the posyandu for pregnant women and toddlers. The great benefit for as many people as possible that will be found in implementation on this program is that there is an insurance effect for program recipients, namely future security guarantees for PKH participants as a means of motivation to see education and health as potential welfare.